ORAL SUFFERING AND ANTIMICROBIAL SUSCEPTIBILITY OF STAPHYLOCOCCUS AUREUS IN A DENTAL HOSPITAL IN KOLKATA, INDIA - BISWAJIT BATABYAL; SHIBENDU BISWAS; BAPPA MANDAL; PRITI D.DESAI; NAVONIL DE SARKAR (International Journal of Pharma and Bio Sciences, 2012)
Staphylococcus aureus is a well recognized pathogen associated with a variety of clinical syndrome. The role of Staph aureus in some types of oral disease may be more important than previously recognized. The present study has been designed to investigate the prevalence of Staphylococcus aureus, MRSA and their rate of resistance to different anti staphylococcal antibiotics. For this study, Gurunanak Institute of Dental Science & Research (Kolkata), selected patients who were suffering from Staphylococcus aureus oral infection. Isolated Staphylococcus aureus was tested for Oxacillin (1 mcg) sensitivity and their antibiotic susceptibility was investigated by using eighteen antibiotics followed by Disk diffusion technique following CLSI method. Out of the 223 specimens collected, 109 (48.9%) were isolated. All the 109 (48.9%) specimens were studied in detail. 5.5% of the isolates were shown to be methicillin resistant Staph. aureus (MRSA). Percentage (%) of resistance in commonly used oral antibiotics are ampicillin 98.1%, amoxycillin/clavulanic acid 73.3%, amoxycillin 45.0%, ofloxacin 48.6% and ciprofloxacin 41.2%. The MRSA isolates showed multiple drug resistance (MDR), except linezolid and imipenem. In line with more recent surveys, this retrospective study suggests that Staph. aureus may be more frequent isolate from the oral cavity than hitherto suspected. The role of Staph.aureus in several diseases of the oral mucosa merits further investigation.